Pediatric versus adult high grade glioma: Immunotherapeutic and genomic considerations - Aggarwal, Payal; Luo, Wen; Pehlivan, Katherine C.; Hoang, Hai; Rajappa, Prajwal; Cripe, Timothy P.; Cassady, Kevin A.; Lee, Dean A.; Cairo, Mitchell S. (Frontiers in Immunology, 2022)
High grade gliomas are identified as malignant central nervous tumors that spread rapidly and have a universally poor prognosis. Historically high grade gliomas in the pediatric population have been treated similarly to adult high grade gliomas. For the first time, the most recent classification of central nervous system tumors by World Health Organization has divided adult from pediatric type diffuse high grade gliomas, underscoring the biologic differences between these tumors in different age groups. The objective of our review is to compare high grade gliomas in the adult versus pediatric patient populations, highlighting similarities and differences in epidemiology, etiology, pathogenesis and therapeutic approaches. High grade gliomas in adults versus children have varying clinical presentations, molecular biology background, and response to chemotherapy, as well as unique molecular targets. However, increasing evidence show that they both respond to recently developed immunotherapies. This review summarizes the distinctions and commonalities between the two in disease pathogenesis and response to therapeutic interventions with a focus on immunotherapy.